Is insulin diluted when stored in water?. Issue 3 (30th January 2016) - Plager, Phillip; Nurie, Kadiro; Omann, Trevor; Moran, Antoinette; Piloya, Thereza; Bahendeka, Silver; Sunni, Muna
Abstract : Background: Insulin storage is a challenge in resource‐poor countries. In Uganda, patients were noted to store insulin vials by submerging them in water. Objective: To examine whether withdrawing insulin from a vial without adding air back causes a vacuum which allows water to enter the vial, resulting in insulin dilution. Methods: Seven hundred units of insulin were withdrawn from forty 10 mL vials of 100 units/mL insulin [20 neutral protamine hagedorn (NPH), 20 regular]. In half, air was added back. The vials were weighed (baseline). Half of the vials (10 with added air, 10 without) were submerged in water for 24 h and then air‐dried for 24 h. Vials that were not submerged sat at room temperature for 48 h. All vials were weighed 48 h from baseline. Results: Addition of air did not impact the change in weight after submersion (air added: −0.002 ± 0.001 g or −0.2 ± 0.1 unit; no air added: −0.003 ± 0.000 g or −0.3 ± 0 unit, p = 0.57). In a subset of vials in which an additional 240 units were withdrawn before submersion for another 24 h, there was still no difference in weight change in those vials with air added (p = 0.2). Conclusion: Withdrawing insulin from a vial without adding air did not result in uptake of water or dilution of insulin in the submerged vial, although it made drawing up the insulin easier. This study did not address the larger concern of bacterial contamination of the rubber stopper during water storage.